Effects of Nano-CaCO3/Limestone Composite Particles on the Hydration Products and Pore Structure of Cementitious Materials - Huashan Yang; Yujun Che (Advances in Materials Science and Engineering)
The agglomeration of nano-CaCO3 (NC) is the largest bottleneck in applications in cementitious materials. If nano-CaCO3 modifies the surface of micron-scale limestone powder (LS), then it will form nano-CaCO3/limestone composite particles (NC/LS). It is known that micron-scale limestone is easily dispersed, and the “dispersion” of NC is governed by that of LS. Therefore, the dispersion of nano-CaCO3 can be improved by the NC/LS in cementitious materials. In this work, the preparation of NC/LS was carried out in a three-necked flask using the Ca(OH)2-H2O-CO2 reaction system. The morphology of NC/LS was observed by a field emission scanning electron microscope (FE-SEM). The effects of NC/LS on the hydration products and pore structure of cementitious materials are proposed. 5% NC/LS was added into cement paste and mortar, and the mechanical properties of the specimens were measured at a certain age. Differential scanning calorimetry (DSC), thermal gravimetric analysis (TG), and backscattered electron imaging (BSE) were conducted on the specimens to investigate the hydration products and pore structure. The properties of specimens with NC/LS were compared to that of control specimens (without NC/LS). The results revealed that NC/LS reduced the porosity and improved the mechanical properties of the cementitious materials.